Tree species diversity of Pegunungan Bintang, Papua, Indonesia as potency of wood supply - AGUSTINUS MURDJOKO; DONY ARISTONE DJITMAU; ELIESER VIKTOR SIRAMI; RIMA HERLINA SETIAWATI SIBURIAN; ANTONI UNGIRWALU; ZULFIKAR MARDIYADI; JIMMY FRANS WANMA; WOLFRAM YAHYA MOFU; JONNI MARWA; CICILIA MARIA ERNA SUSANTI; MAX JONDUDAGO TOKEDE; CHRISTIAN SOLEMAN IMBURI; MEKY SAGRIM; HANS MAMBOAI; LUKAS YOWEL SONBAIT; FEBRIZA DWIRANTI; YENNY YENDRI SALOSA; JOHANA BETY PAEMBONAN; ESTIKO TRI WIRADYO; ERNI UNENOR; NITHANEL MIKAEL HENDRIK BENU; ANDI SASTRA BENNY SARAGIH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Murdjoko A, Djitmau DA, Sirami EV, Siburian RHS, Ungirwalu A, Mardiyadi Z, Wanma JF, Mofu WY, Marwa J, Susanti CME, Tokede MJ, Imburi CS, Sagrim M, Mamboai H, Sonbait LY, Dwiranti F, Salosa YY, Paembonan JB, Wiradyo ET, Unenor E, Benu NMH, Saragih ASB. 2021. Tree species diversity of Pegunungan Bintang, Papua, Indonesia as potency of wood supply. Biodiversitas 22: 5645-5655. The tropical rainforest is a primary global concern in many aspects. Therefore, this study aimed to describe the tree diversity in Pegunungan Bintang Forest, Papua, Indonesia. There are 10 dominant species from seedlings, saplings, poles, and trees, indicating the timber production potency. This study set systematic plots in Murkim and Teiraplu Sub-districts to collect taxonomic information, diameter, and clear bole height samples. The results showed that the forest was categorized as a tropical mixed due to diverse tree species. The leading plant families included Moraceae, Myrtaceae, Euphorbiaceae, Lauraceae, and Anacardiaceae, with various seedlings, saplings, poles, and trees. The potency of timber was reflected through sample distribution using the reverse J-shaped curve, identifying the merchantable trees with larger and smaller diameters as re-established. However, timber utilization management requires silvicultural treatments using selective logging by diameter limit and logging cycle for forest sustainability.